Peters Plus syndrome: a recognizable clinical entity - Demir, Gizem Ürel; Lafcı, Naz Güleray; Doğan, Özlem Akgün; Şimşek Kiper, Pelin Özlem; Utine, Gülen Eda (The Turkish Journal of Pediatrics, 2020)
Peters plus syndrome is a rare genetic condition wherein multiple systemic involvement with distinctive facial features are manifested, whilst the hallmark is Peters anomaly, occuring from anterior segment dysgenesis. Homozygous variants in the B3GLCT gene were identified to underlie this disorder. We here report on a onemonth- old female patient with typical features characteristic of Peters plus syndrome in whom a homozygous pathogenic mutation in the B3GLCT gene was detected.